Analysis of the Distribution of Fertilizer Commodities through Multimodal Transportation: West Java, East Java and South Sumatra - Indira Shaffiyah (Journal of Logistics and Supply Chain, 2023)
The need for both organic and inorganic fertilizers in Indonesia continues to increase, in line with increasing demand from the plantation and agricultural sectors. This also results in supplies from subsidized fertilizer production and fertilizer from large industries sometimes note being capable to meet the market. In this scientific article, we will discuss the design and planning of fertilizer distribution from both large industries and small and medium industries which will be reviewed from the distribution of goods in 3 provinces zones which are estimated to have quite high movement of fertilizer products. The method used in this study in general is a literature review where the search for sources and data is carried out by literature study. In the three review zones, the distribution process carried out depends on the amount of production and existing demand. After analyzing the distribution of fertilizer commodities, the results were obtained in the form of growth, production capacity, BOOK and transportation rates for each zone.